Matter of margins. (30th July 2014) - Gualdi, G.; Monari, P.; Crotti, S.; Damiani, G.; Facchetti, F.; Calzavara‐Pinton, P.; Fantini, F.
Abstract: Background: Basal cell carcinoma (BCC) is the most common cancer, it represents a significant economic burden to health services because of a large volume of affected patients. Surgical excision with histological assessment of the surgical margins is widely considered as the mainstay of BCC treatment. Incomplete removal, in fact, should be considered a poor prognostic indicator, as incomplete removal of lesions is at risk of local recurrence. Actually, dermatological surgeries are carried out by a variety of different types of practitioners, such as plastic surgeons, maxillofacial surgeons, otorhinolaryngologists, ophthalmologists and finally dermatologists. Incomplete removal of the tumour ranges from 6.3% to 25%, depending on the improper intra‐operative evaluation of the extent of the tumour. It depends on the clinical knowledge derived from both training and daily experience. In this sense, the majority of the largest studies derive from plastic surgeons, while dermatologists have small case series, albeit with a higher therapeutic efficacy in terms of complete surgical excision. Objectives: We conducted a retrospective analysis of the surgical activity, more specifically we evaluated both our therapeutic accuracy and analyzed the prognostic factors related to incomplete excisions. Methods: A retrospective review of all BCC removals was performed. A total of 4523 BCC removals were included; other neoplasm, benign lesions and biopsies were also excluded. Each BCC's size diameter, localization, histology and histological presence of complicating factors was assessed, then the percentage of the incomplete removal was calculated. Results: Incomplete resections occurred in 225 (4.97%) BCCs of the cases. Thirteen areas were categorized into in three different levels that rank the risk of incomplete removals. Sub‐analysis indicates that just over a third had no complicating factors with the lateral/deep margins. The most frequent complicating factor is ulceration (22.9%), while vascular invasion or seborrheic keratoses were not found. Actinic keratoses, scabs and scars held the most responsibility for the involvement of the lateral margins, while perineural invasion is the main factor leading to deep margin involvement. Finally, a different trend for the involvement of lateral or deep margins according different histological sub‐types was highlighted; lateral involvement is more frequent for the infiltrative/morpheic type, while the deep margin is more involved in the nodular type.